Analysis of the Right to Food from a Legal and Policy Perspective on Ensuring Food Security in India (International Journal of Food and Nutritional Sciences, 2022)
The right to food is a fundamental human right that plays a crucial role in ensuring the wellbeing and dignity of individuals. In India, the realization of this right has evolved through historical contexts, legal frameworks, and various government schemes aimed at addressing food security. This paper examines the significance of the right to food from an Indian perspective, highlighting the challenges faced by vulnerable groups, including women, children, tribal communities, and migrant workers. It also explores the role of the judiciary and civil society in advocating for food security, as well as India’s commitments to international frameworks, such as the United Nations Sustainable Development Goals (SDGs). Furthermore, the paper provides recommendations for enhancing agricultural productivity, technological interventions in food distribution, and improving governance in food security programs. By addressing these challenges and implementing effective policies, India can move closer to achieving food security for all its citizens.